THE PRINCIPLE OF GOOD FAITH AS ONE OF THE PRINCIPLES OF IMPLEMENTATION OF ADMINISTRATIVE PROCEDURAL RIGHTS - Yatsuba, Volodymyr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to the study of the principle of good faith as one of the principles of implementation of administrative procedural rights. It is indicated that the problem of forming effective ways to protect the rights, freedoms, legitimate interests of a person and a citizen, as well as a legal entity, has become urgent for Ukraine since its independence. Research methods: the chosen topic of scientific research requires the use of various scientific methods and approaches to obtain high-quality results. Therefore, the following research methods were used to solve the tasks set: analysis; systematic method; analytical method, etc. Results: аccording to Article 3 of the Constitution of Ukraine, it is determined that the priority task of the functioning of the state is to ensure and protect human rights and freedoms as the main social value. Such a normative and legal provision of the Constitution of Ukraine establishes the substantive functional purpose of the state, determines the direction of implementation of functions and methods of public administration. The definition of a person as the highest social value is the basis for the implementation of the mechanism of responsibility of the state and its institutions to the individual at the appropriate level. The application of the mechanism of state responsibility, in addition to its constitutional consolidation, requires the development of effective structures capable of making such a norm a reality. Discussion: the components of the principle of good faith in administrative proceedings are: 1) prohibition of abuse of procedural rights; 2) the requirement of conscientious fulfillment of procedural obligations; 3) prohibition of contradictory conduct of the parties, or the rule of procedural estoppel; 4) prohibition to impose other unlawful obstacles in the administration of justice. The principle of good faith is a general principle of law that applies to the entire sphere of legal regulation, including the sphere of administrative proceedings.